Inventor CEO involvement and firm exploitative and exploratory innovation - Harrison, Joseph S.; Boivie, Steven; Stern, Ithai; Porac, Joseph (Strategic Management Journal, 2024)
Abstract Research Summary This study extends recent findings that inventor CEOs increase innovative output in large established firms by examining how their involvement in the innovative process influences the nature of innovations produced. Our theory suggests that inventor CEOs who take a hands‐on approach to innovation lead their firms to engage in more exploitative rather than exploratory innovation. We further posit that this effect is particularly strong for insider inventor CEOs, and especially founders, but weaker for outsiders and when the firm's board has broader industry experience. Using a sample of S&P 1500 firms from 1994 to 2010 and inventor CEOs' engagement in patenting as an indicator of hands‐on involvement, we find considerable support for our predictions. Managerial Summary CEOs with hands‐on experience innovating can substantially increase innovative output in large established firms. Yet, we show that inventors who remain directly engaged in their firms' innovation activities as CEO can limit their scope to incremental innovations that exploit existing technologies as opposed to more radical innovations that result in novel product or service offerings. These tendencies are stronger for inventors who come to the CEO position from inside the firm, especially founders, but weaker when the firm's board has broader industry experience. Overall, our study reveals an important tradeoff for large firms of having an inventor as CEO, how hands‐on involvement by inventor CEOs may narrow their firms' innovative trajectories, and how or when these tendencies can be mitigated.